A randomized controlled trial to study the effect of supplemental premilking stimulation on milking performance, teat tissue condition, udder health, and well-being in dairy cows - A. Singh; M.E. Spellman; H. Somula; J.A. Valdevieso; R. Palme; M. Wieland (Journal of Dairy Science)
ABSTRACT: The objectives of this study were to evaluate the effect of supplemental premilking stimulation, provided after manual stimulation, by means of high-frequency pulsation without reduction of the vacuum in the pulsation chamber on milking performance, teat tissue condition, udder health, and well-being in dairy cows. In a randomized controlled trial, Holstein cows (n = 491) from 1 commercial dairy farm with a thrice-daily milking schedule were assigned to treatment and control groups over a 64-d period. Treatments consisted of a maximum of 20 s of pulsation stimulation at a pulsation rate of 100 (SPS100) or 300 (SPS300) cycles per minute and a pulsation ratio of 25:75. The treatments were applied after completion of manual premilking stimulation upon milking unit attachment. Cows in the control group (CON) received only traditional premilking stimulation by manual forestripping and wiping for 6 s. Milking characteristics were measured with on-farm milk flow meters. Milking machine-induced short-term (swelling at teat base, firmness at teat end, and teat discoloration) and long-term (teat-end callosity) changes to the teat tissue were assessed manually and visually. Composite milk samples were analyzed for SCC. Cow hind-leg activity was assessed with 3-dimensional accelerometers. Fecal 11,17-dioxoandrostanes (11,17-DOA; a group of cortisol metabolites) were determined on wk 4 and 8 to assess the well-being of the cows. Generalized linear mixed models were used to study the effect of treatments on the outcome variables milk yield per milking and milking unit-on time. We observed no meaningful differences among groups for milk yield or milking unit-on time. Least squares means and their 95% CI for cows in the SPS100, SPS300, and CON groups were 13.9 (13.3–14.5), 14.0 (13.4–14.6), and 13.9 (13.3–14.6) kg for milk yield and 218 (212–224), 218 (211–224), and 218 (212–224) s for milking unit-on time, respectively. Compared with cows in the CON group, the odds (95% CI) of short-term changes were 1.30 (0.95–1.78) for the SPS100 group and 1.50 (1.10–2.05) for the SPS300 group. The odds of long-term changes were 0.94 (0.67–1.34) for cows in the SPS100 group and 0.71 (0.49–1.04) for cows in the SPS300 group. We observed no differences in SCC. In reference to the CON group, the hazard ratio (95% CI) in SPS100 and SPS300, respectively, were 0.35 (0.13–0.98) and 1.22 (0.57–2.64) for clinical mastitis, and 0.34 (0.12–0.95) and 1.28 (0.60–2.73) for culling. The LSM (95% CI) of hind-leg activity during milking were 8.3 (6.5–10.5), 10.6 (8.1–13.7), and 9.1 (7.2–11.6) movements per milking for the SPS100, SPS300, and CON groups, respectively. The LSM (95% CI) of fecal 11,17-DOA concentration (ng/g) at the first and second test days, respectively, were 31.1 (28.1–34.2) and 22.3 (19.2–25.4) for the SPS100 group, 26.4 (23.4–29.4) and 25.2 (22.0–28.4) for the SPS300 group, and 24.8 (21.8–27.9) and 25.0 (21.7–28.3) for the CON group. We conclude that applying supplemental stimulation after manual stimulation through the high-frequency pulsation system tested here did not impart additional benefits to the milk harvesting process, teat tissue condition, somatic cell count, or the well-being of the animals.